Deskripsi Kemampuan Literasi Matematika Siswa Kelas VIII SMP Negeri 1 Malunda Kabupaten Majene - Ahmad Talib; Usman Mulbar; Widyarti Hakman (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2023)
This research is qualitative research with a descriptive approach aimed at describing the mathematical literacy skills of class VIII students of SMP Negeri 1 Malunda, Majene Regency. There are 6 subjects selected based on high, medium and low mathematical abilities. Data collection techniques used were tests and interviews. The instruments used in obtaining the data were tests of mathematical literacy skills and interviews. The data analysis techniques used are data condensation, data presentation and conclusion. The results showed that of the 6 levels of mathematical literacy ability in PISA, students with high mathematical abilities fulfilled 3 levels, students with moderate mathematical abilities fulfilled 1 level, and students with low mathematical abilities did not fulfill the 6 levels of mathematical literacy ability in PISA.